Vider, Stephen. The Queerness of Home. Gender, Sexuality & the Politics of Domesticity after World War II. Chicago, The University of Chicago Press, 2021. ISBN-13: 978-0-226-80839-9. 300 páginas - Jiménez-Leciñena, Javier (Investigaciones Feministas, 2022)
Reseña de la obra de Vider, Stephen. The Queerness of Home. Gender, Sexuality & the Politics of Domesticity after World War II. Chicago, The University of Chicago Press, 2021. ISBN-13: 978-0-226-80839-9. 300 páginas